Downregulation of DEPTOR inhibits the proliferation, migration, and survival of osteosarcoma through PI3K/Akt/mTOR pathway - Hu B (OncoTargets and Therapy, 2017)
Binwu Hu,1,* Xiao Lv,1,* Feng Gao,1 Songfeng Chen,2 Shangyu Wang,1 Xiangcheng Qing,1 Jianxiang Liu,1 Baichuan Wang,1 Zengwu Shao1 1Department of Orthopaedics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 2Department of Orthopaedic Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, China *These authors contributed equally to this work Abstract: Accumulating evidence reveals that DEP-domain containing mTOR-interacting protein (DEPTOR) plays pivotal roles in the pathogenesis and progression of many tumors. However, the expression level of DEPTOR and its function in the tumorigenesis of osteosarcoma (OS) remain unknown. In this study, we conducted quantitative real-time polymerase chain reaction, Western blot, and immunohistochemistry to detect DEPTOR expression level in human OS tissues and cell lines. To assess DEPTOR function, DEPTOR siRNA was designed and transfected into OS cells, which were then used in a series of in vitro assays. Our results indicated that DEPTOR was highly expressed in some OS tissues and cell lines. DEPTOR knockdown by siRNA dramatically inhibited cell proliferation, migration, invasion, and the formation of vasculogenic mimicry in OS cells. In addition, DEPTOR knockdown induced cell cycle arrest in the G0/G1 phase and apoptosis in the OS cell lines, MG63 and MNNG/HOS. Furthermore, we found that DEPTOR knockdown notably activated mTOR and inhibited the PI3K/Akt pathway. Taken together, these results suggest that DEPTOR overexpression is necessary for the proliferation, migration, invasion, formation of vasculogenic mimicry, and survival of OS cells and may be a potential target for the treatment of OS. Keywords: osteosarcoma, DEPTOR, PI3K/Akt/mTOR pathway, proliferation, apoptosis